Histopathology of the effect of x-rays on renal tissue of rattus rattus var. Albinus with a diet reinforced with triticum aestivum (wheat) - Rodríguez Vega, Juan Luis (2016)
The purpose of the present investigation was to determine the effect of X-rays on the mucosa Gastric cancer in Rattus Rattus var. Albinus with a diet enhanced with Triticum Aestivum (wheat) ". Twenty-four adult male albino rats weighing between 200 and 250 g were used, which were randomly distributed into two groups: control and experimental, with 12 animals each. The control group was subdivided randomly into 2 subgroups, the D: which did not receive wheat and was not irradiated, and the B: which did not receive wheat but was irradiated. The Experimental group was subdivided randomly into 2 subgroups, the C: which received wheat and was not irradiated and the A: which received wheat and if it was irradiated. Oral administration of wheat was performed during 16 days prior to X-ray irradiation, 18 mSv, the animals were housed in cages, anesthetized with 0.6% pentobarbital in doses of 0.5 ml / kg p.c., v.i.p and then taken to the X-rays in the ESSALUD - El Porvenir - La Libertad Center and a radiation shot. It concludes that the diet with Triticum aestivum (wheat) avoids the cellular damage of the X radiation, in the esophagus of Rattus rattus var. Albinus.